2011
DOI: 10.1142/s0219498811005233
|View full text |Cite
|
Sign up to set email alerts
|

SOLUBLE MAXIMAL SUBGROUPS IN GLn(D)

Abstract: Let D be an F -central non-commutative division ring. Here, it is proved that if GLn(D) contains a non-abelian soluble maximal subgroup, then n = 1, [D : F ] < ∞, and D is cyclic of degree p, a prime. Furthermore, a classification of soluble maximal subgroups of GLn(F ) for an algebraically closed or real closed field F is also presented. We then determine all soluble maximal subgroups of GL 2 (F ) for fields F with Char F = 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In fact, they showed that if the cardinality of F is greater than 3α(w) 2 , then D = F . Recently, there are some articles on some subgroups of D * which satisfy a group identity or some special group identity (see [7,10,12,14]): Ramezan-Nassab and Kiani proved in [14] that subnormal subgroups of D * satisfying the n-Engel condition are contained in F . It is proved in [12] that every maximal subgroup of D * satisfying a group identity is the multiplicative group of a maximal subfield of…”
Section: Introductionmentioning
confidence: 99%
“…In fact, they showed that if the cardinality of F is greater than 3α(w) 2 , then D = F . Recently, there are some articles on some subgroups of D * which satisfy a group identity or some special group identity (see [7,10,12,14]): Ramezan-Nassab and Kiani proved in [14] that subnormal subgroups of D * satisfying the n-Engel condition are contained in F . It is proved in [12] that every maximal subgroup of D * satisfying a group identity is the multiplicative group of a maximal subfield of…”
Section: Introductionmentioning
confidence: 99%
“…Our object here is to discuss the general skew linear groups whose maximal subgroups are of some special types. Some properties of maximal subgroups of GL n (D) have been studied in a series of papers, see, e.g., [1,2,3,7,12,13]. In all of those papers, authors attempted to show that the structure of maximal subgroups of GL n (D) is similar, in some sense, to the structure of GL n (D).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, if D is an infinite division ring, in [3] it was shown that every nilpotent maximal subgroup of GL n (D) is abelian, and in [13] the authors proved that for n ≥ 2, every locally nilpotent maximal subgroup of GL n (D) is abelian. Also, if D is non-commutative and n ≥ 2, in [2] it was shown that every soluble maximal subgroup of GL n (D) is abelian, and in [13] the authors proved that for n ≥ 3, every locally soluble maximal subgroup of GL n (D) is abelian. For some recent results see [12].…”
Section: Introductionmentioning
confidence: 99%
“…Now, we would like to know whether or not an Engel maximal subgroup of GL m .D/ is abelian. Recently, it was shown in [5] that if D is a non-commutative division ring and m > 1, then every soluble maximal subgroup of GL m .D/ is abelian. In the next theorem we extend this result as follows: Corollary 1.7.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore M is soluble. Now, if F OEM ¤ D, by [5,Theorem 3.7] M is abelian. Thus let F OEM D D. Then [5,Theorem 3.6] implies that dim F D < 1, which implies that M is abelian.…”
Section: Introductionmentioning
confidence: 99%